2009
DOI: 10.1509/jmkr.46.5.573
|View full text |Cite
|
Sign up to set email alerts
|

Buyer Monitoring: A Means to Insure Personalized Service

Abstract: Marketing scholars have proposed that service employees play a primary role in delivering service quality. However, the question of how to motivate service employees to enhance service production has received little research attention. The authors address this gap by advocating a control mechanism first discussed in the economics literature—buyer monitoring. The authors focus on a pervasive form of buyer monitoring, voluntary tipping, and examine the effectiveness of this control mechanism as a means for impro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
82
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 62 publications
(87 citation statements)
references
References 53 publications
(102 reference statements)
4
82
1
Order By: Relevance
“…While there has been substantial debate in the literature regarding whether the act of tipping improves service quality (Azar, 2008;Kwortnik et al, 2009;Lynn and McCall, 2000), the findings herein suggest that tipping motivation is more self-centered and intrinsically contrived than previously elucidated in the literature. Inasmuch, it is suggested that future research on tipping motivation should include efforts to further develop the constructs identified in this inquiry and apply them in experimental settings.…”
Section: Resultsmentioning
confidence: 52%
See 2 more Smart Citations
“…While there has been substantial debate in the literature regarding whether the act of tipping improves service quality (Azar, 2008;Kwortnik et al, 2009;Lynn and McCall, 2000), the findings herein suggest that tipping motivation is more self-centered and intrinsically contrived than previously elucidated in the literature. Inasmuch, it is suggested that future research on tipping motivation should include efforts to further develop the constructs identified in this inquiry and apply them in experimental settings.…”
Section: Resultsmentioning
confidence: 52%
“…From a pragmatic perspective, since tipping is a significant economic activity (Azar, 2008;Kwortnik et al, 2009), it is important for both managers and tipped service employees to better understand the multiple underlying dimensions that influence tipping motivation. From both perspectives, understanding the issues that motivate tipping behavior could lead to an increase in the number of patrons that leave tips and possibly an increase in tip amounts.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Second, research indicates that consumers believe tips are incentives that improve service (Mills and Riehle, 1987), so replacing voluntary tipping with service charges may reduce expectations for service quality, which in turn affect perceptions of service through assimilation (Herr et al, 1983) and/or expectancy effects (Rosenthal and Rubin, 1978). Third, a series of studies by Kwortnik et al (2009) found that voluntary tipping policies improve service levels by motivating servers to deliver friendlier and more personalized service, and a study by Lynn et al (2011) found that tipping helps to attract and retain more motivated and capable staff; taken together, these studies suggest that replacing voluntary tipping with service charges may reduce customer satisfaction by lowering actual service levels. With all of these theoretical processes pointing in the same direction, we hypothesize:…”
Section: Introductionmentioning
confidence: 99%
“…From a practical perspective, tipping affects the experiences of consumers (Mills and Riehle, 1987), the incomes and motivation of service workers (Kwortnik et al, forthcoming;Lynn, 2002), and ultimately the performance and profitability of service businesses (Lynn and Withiam, 2008;Schwartz, 1997). A better understanding of the determinants of tipping would inform servers' efforts to increase their incomes (Lynn, 2004a,b), managers' efforts to train and motivate their service employees (Azar, 2004a;Lynn, 2005), and executives' efforts to set optimal tipping policies (Azar, 2003;Lynn, 2008).…”
Section: Introductionmentioning
confidence: 99%